Overload and Overtraining
This issue of Coaching Science Abstracts relates research and thoughts associated with how hard an athlete should work (overload) and under what conditions a persistent overload cannot be tolerated (overtraining). The two concepts are intermixed since one is a cause of the other. The impact of these abstracts is to support the Roux Principle: light training loads are useless, moderate loads are beneficial, and excessive loads are harmful. The articles are: 1. TYPES OF MUSCLE FIBERS AND FORCE Rushall Thoughts (1992). 2. DALDA AND TRAINING MEASURES Rushall Thoughts (1992). 3. MACROCYCLE PLANNING FOR TEAM SPORTS Rushall Thoughts (1992). 4. HELL WEEKS Costill, D. L. & King, D. S. (1983). Workout evaluation. Swimming Technique, August-October, 24-27. 5. WHEN TO APPLY OVERLOADS Carlile, F. (personal communication, July 8, 1991). 6. SYMPTOMS OF OVERTRAINING STRESS Parker, J. (1989). Wiping your swimmers out. Swimming Technique, May-July, 10-16. 7. TRAINING OVERLOAD Costill, D. L., Flynn, M. G., Kirwan, J. P., Houmard, J. A., Mitchell, J. B., Thomas, R., & Park, S. H. (1988). Effects of repeated days of intensified training on muscle glycogen and swimming performance. Medicine and Science in Sports and Exercise, 20, 249-254. 8. EXTRA SWIMMING TRAINING PRODUCES NO ADDED BENEFITS Kirwan, J. P., Costill, D. L., Flynn, M. G., Mitchell, J. B., Fink, W. J., Neufer, P. D., & Houmard, J. A. (1988). Physiological responses to successive days of intense training in competitive swimmers. Medicine and Science in Sports and Exercise, 20, 255-259. 9. REDUCED TRAINING AND EFFECTS ON STRENGTH AND ENDURANCE Neufer, P. D., Costill, D. L., Fielding, R. A., Flynn, M. G., & Kirwan, J. P. (1987). Effects of reduced training on muscular strength and endurance in competitive swimmers. Medicine and Science in Sports and Exercise, 19, 486-490. 10. TRAINING AND STIMULUS REQUIREMENTS FOR SWIMMING Troup, J. P. (Ed.). (1990). Selection of effective training categories. In International Center For Aquatic Research annual: Studies by the International Center for Aquatic Research 1989-90. Colorado Springs, CO: United States Swimming Press. 11. ON HOW HARD TO WORK Time, 3 August, 1992, pp. 58-63. 12. MUSCLE THEORY Phillips, E. (1992). No simple explanation for Kenyan's dominance-running. San Diego Union-Tribune, 17 June, p. D-2. 13. COMMENTS ON TRAINING Rushall Thoughts, 1993. 14. DETRAINING, HEART RATES, AND STROKE VOLUME Neufer, P. D. (1989). The effect of detraining and reduced training on the physiological adaptations to aerobic exercise training. Sports Medicine, 6, 302-321. 15. OVERTRAINING Wilmore, J. H., & Costill, D. L. (1988). Training for sport and activity. Chapter 11. Dubuque, IA: Wm C. Brown. 16. CARBOHYDRATES AND OVERTRAINING Snyder, A. C., Kuipers, H., Cheng, B., Servais, R., & Fransen, E. (1993). Indices of over-reaching following intensified training: role of carbohydrate intake. Medicine and Science in Sports and Exercise, 25(5), Supplement abstract 966. 17. TAPERING Wilmore, J. H., & Costill, D. L. (1988). Training for sport and activity. Chapter 11. Dubuque, IA: Wm C. Brown. 18. SERUM FERRITIN AND INJURIES Loosli, A. R., Requa, R. K., & Garrick, J. G. (1993). Serum ferritin and injuries in female high school cross country runners. Medicine and Science in Sports and Exercise, 25(5), Supplement abstract 129. 19. IRON DEPLETION PROBLEM Kluger, M. J., Ashtron, H. A., Doshi, J. B., Hein, P. S., Newby, J. S., & Philips, R. S. (1992). Letters to the Editor-in-chief. Medicine and Science in Sports and Exercise, 24, 303-304. 20. HORMONAL RESPONSES TO OVERTRAINING IN SWIMMERS Hooper, S. L., MacKinnon, L. T., Gordon, R. D., & Bachman, A. W. (1993). Hormonal response of elite swimmers to overtraining. Medicine and Science in Sports and Exercise, 25, 741-747. 21. RUSSIAN SWIMMERS, WEIGHT TRAINING, LEVELS OF WORK, AND CENTRALIZED TRAINING Ewald, R. (1994). The Russian capitalists. Swimming World and Junior Swimmer, 35(3), 33-42. 22. TESTING FOR OVERTRAINING Rushall Thoughts, 1993 (from a commentary to Forbes Carlile). 23. FURTHER ON HEART RATES Rushall Thoughts (1993). 24. PSYCHOLOGY INDICATES OVERTRAINING IN SWIMMING Lowensteyn, I., Signorile, J. F., Kwiatkowski, K., Caruso, J., Ferris, D., Salhanick, D., Perry, A., & Mancino, C. (1994). Examination of various biological parameters in response to a season of training in competitive swimmers. Medicine and Science in Sports and Exercise, 26(5), Supplement abstract 669. 25. TRAINING VOLUME DECREASES PRODUCE AN EFFECTIVE TAPER Zarkadas, P. C., Carter, J. B., & Bannister, E. W. (1994). Taper increases performance and aerobic power in triathletes. Medicine and Science in Sports and Exercise, 26(5), Supplement abstract 194. 26. TAPER BY DOING THE ACTIVITY Houmard, J. A., Scott, B. K., Justice, C. L., & Chenier, T. C. (1994). The effects of taper on performance in distance runners. Medicine and Science in Sports and Exercise, 26(5), 624-631. 27. COMPONENTS OF A SWIMMING TAPER Houmard, J. A., & Johns, R. A. (1994). Effects of taper on swim performance: practical implications. Sports Medicine, 17, 224-232. 28. INSTITUTIONALIZED OVERTRAINING Rushall Thoughts (1994). 29. PERCENTAGE OF VO2max USED IN ENDURANCE EVENTS Noakes, T. (1986). Lore of running. Cape Town, South Africa: Oxford University Press. (p. 40). 30. REDUCED RUNNERS' WORKLOAD MAINTAINS TRAINING EFFECTS Houmard, J. A., Costill, D. L., Mitchell, J. B., Park, S. H., Hickner, R. C., & Roemmich, J. N. (1990). Reduced training maintains performance in distance runners. International Journal of Sports Medicine, 11, 46-52. 31. TRAINING STRESS MARKERS Flynn, M. G., Pizza, F. X., Boone, J. B. Jr., Andres, F. F., Michaud, T. A., & Rodriguez-Zayas, J. R. (1994). Indices of training stress during competitive running and swimming seasons. International Journal of Sports Medicine, 15, 21-26. 32. WHAT VO2max MEASURES Boulay, M. R., Barbeau, P., Giroux, M., Prud'homme, D., & Simoneau, J. A. (1992). Peripheral and central adaptations in cyclists during a training and competitive season. Medicine and Science in Sports and Exercise, 24(5), Supplement abstract 566. 33. ONE MORE TIME: ARE THERE MEASURES THAT ARE SENSITIVE TO OVERTRAINED OR HIGHLY FATIGUED STATES? Hooper, S. L., MacKinnon, L. T., Howard, A, Gordon, R. D., & Bachmann, A. W. (1995). Markers for monitoring overtraining and recovery. Medicine and Science in Sports and Exercise, 27, 106-112. 34. OVERTRAINED STATE NOT RELATED TO GLYCOGEN STATE Snyder, A. C., Kuipers, H., Cheng, B., Servais, R., & Fransen, E. (1995). Overtraining following intensified training with normal muscle glycogen. Medicine and Science in Sports and Exercise, 27, 1063-1070. 35. A MEASURE OF STRESS RESPONSE IN ATHLETES Rushall, B. S. (1990). A tool for measuring stress tolerance in elite athletes. Applied Sport Psychology, 2, 51-66. 36. SUGGESTED READING Rushall, B. S., & Pyke, F. S. (1990). Training for sports and physical fitness. Melbourne, Australia: Macmillan Educational. 37. PSYCHOLOGY MEASURES TRAINING STRESS AND FATIGUE Theriault, D., Lacoste, E., Gadoury, M., Richard, D., Tremblay, A., Labrie, A., Leblanc, C., & Theriault, G. (1995). Early detection and prevention of stress and fatigue in elite athletes: The use of psychological and clinical measurement instruments. Medicine and Science in Sports and Exercise, 27(5), Supplement abstract 167. 38. BLOOD FEATURES AND OVERTRAINING Urhausen, A., Gabriel, H., & Kindermann, W. (1995). Blood hormones as markers of training stress and overtraining. Sports Medicine, 20, 251-276. 39. EXCESSIVE ANAEROBIC TRAINING CAUSES OVERTRAINING Urhausen, A., Gabriel, H. & Kindermann, W. (1995). Blood hormones as markers of training stress and overtraining. Sports Medicine, 20, 251-276. 40. AFFECTS OF INCREASED TRAINING VOLUME Costill, D. L., Thomas, R., Robergs, R. A., Pascoe, D., Lambert, C., Barr, S. & Fink, W. J. (1991). Adaptations to swimming training: Influence of training volume. Medicine and Science in Sports and Exercise, 23, 371-377.